8th International Munich Chassis Symposium 2017 chassis.tech plus - Pfeffer, Prof. Dr. Peter E. (Proceedings,, 2017)
You can find in this book the development of highly and fully automatic driving and the increasing electrification of the powertrain now face chassis development with new challenges too. Innovative chassis systems have to provide solutions for automated driving. The efficient chassis of the future also has to keep an eye on CO2 targets, comfort and customer focus at all times. A modern chassis has to provide for this in the form of innovations while taking the physical and mechanical interdependencies into account. Confronting these new developments is a challenge for simulation and testing. Contents New chassis.- Chassis components and historical aspects.- Development methods.- Driving comfort.- High-performance brakes and test methods.- Brake wear particle emissions and materials.- Chassis control systems.- Brake systems of the future.- Virtual development methods.- Objective assessments.- Steering systems and functions.- Virtual development methods.- Developmental aims and objectification.- Tire testing and simulation.- Steering feel.- Wheel technologies and trends. Target audiences Automotive engineers and chassis specialists as well as students looking for state-of-the-art information regarding their field of activity - Lecturers and instructors at universities and universities of applied sciences with the main subject of automotive engineering - Experts, researchers and development engineers of the automotive and the supplying industry Publisher ATZ live stands for top quality and a high level of specialist information and is part of Springer Nature, one of the leading publishing groups worldwide for scientific, educational and specialist literature.Partner TÜV SÜD is an international leading technical service organisation catering to the industry, mobility and certification segment.